History of Korea: A Captivating Guide to Korean History, Including Events Such as the Mongol Invasions, the Split into North and South, and the Korean War (Captivating History, 2020)
Collects the inspiring contributions of Korea's contemporary Zen Masters, including koans and excerpts of Q-and-A conversations between them and students and other teachers. Original.
Keywords: South Korean History